Blockbuster TV : Must-See Sitcoms in the Network Era. - Staiger, Janet (NYU Press, 2000)
Archie Bunker. Jed. Laverne and Shirley. Cliff Huxtable. Throughout the entire history of American prime-time television only four sitcoms have been true blockbusters, with Nielsen ratings far above the second- and third-rated programs. Weekly, millions of Americans of every age were making a special effort to turn on the set to see what Archie, Jed, Laverne, and Cliff were doing that week. The wild popularity of these shows-- All in the Family, The Beverly Hillbillies, Laverne & Shirley (and its partner Happy Days), and The Cosby Show --left commentators bewildered by the tastes and prefer.